If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -2(x + 7) = -4x + -12 Reorder the terms: 6 + -2(7 + x) = -4x + -12 6 + (7 * -2 + x * -2) = -4x + -12 6 + (-14 + -2x) = -4x + -12 Combine like terms: 6 + -14 = -8 -8 + -2x = -4x + -12 Reorder the terms: -8 + -2x = -12 + -4x Solving -8 + -2x = -12 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. -8 + -2x + 4x = -12 + -4x + 4x Combine like terms: -2x + 4x = 2x -8 + 2x = -12 + -4x + 4x Combine like terms: -4x + 4x = 0 -8 + 2x = -12 + 0 -8 + 2x = -12 Add '8' to each side of the equation. -8 + 8 + 2x = -12 + 8 Combine like terms: -8 + 8 = 0 0 + 2x = -12 + 8 2x = -12 + 8 Combine like terms: -12 + 8 = -4 2x = -4 Divide each side by '2'. x = -2 Simplifying x = -2
| 71.77=c+36.82 | | (x-y)*y(dx)=x^2(dy) | | 2-20f=-19f-10 | | =(5x^5+4x^4+6)-(-12x^4+8x^5-18) | | 5a-4a=14 | | 18h=20+19h | | (2x^3-5x^2+7x)(-x^2y)= | | w-6.38=4.85 | | 10b+7+18=7+9b | | q+30=6q | | 3(2t-4)=-4(x+1) | | 5-3(x-3)=2(2-x)-8 | | -10p+8=-6-8p-4p | | 2n-4n=30 | | 14=-4+9x | | 5x-3y=42 | | 10+m=-10-3m | | 3+2u=11 | | 5x-15xy+xz= | | 13j-12j=19 | | 13j-12j= | | 12x+59=x+70 | | 75+50x=25+75x | | 2x+17=14+x | | 7-d/4=5/2 | | -3(t-3)+7t=8t-2 | | 2(x+4)+3x=183 | | (12x+6)=5x | | 10=p/10 | | y=36(1/2) | | 8x^2+44-16=0 | | A[n]=2n+5 |